Determining Safe Participation in Aerobic Exercise Early After Stroke Through a Graded Submaximal Exercise Test. Issue 9 (3rd June 2020) - Inness, Elizabeth L; Aqui, Anthony; Foster, Evan; Fraser, Julia; Danells, Cynthia J; Biasin, Louis; Brunton, Karen; Howe, Jo-Anne; Poon, Vivien; Tang, Ada; Mansfield, Avril; Marzolini, Susan; et al.
Abstract: Objective: The benefits of aerobic exercise early after stroke are well known, but concerns about cardiovascular risk are a barrier to clinical implementation. Symptom-limited exercise testing with electrocardiography (ECG) is recommended but not always feasible. The purpose of this study was to determine the frequency of and corresponding exercise intensities at which ECG abnormalities occurred during submaximal exercise testing that would limit safe exercise prescription beyond those intensities. Methods: This study was a retrospective analysis of ECGs from 195 patients who completed submaximal exercise testing during stroke rehabilitation. A graded submaximal exercise test was conducted with a 5- or 12-lead ECG and was terminated on the basis of predetermined endpoint criteria (heart rate, perceived exertion, signs, or symptoms). ECGs were retrospectively reviewed for exercise-induced abnormalities and their associated heart rates. Results: The peak heart rate achieved was 65.4% (SD = 10.5%) of the predicted maximum heart rate or 29.1% (SD = 15.5%) of the heart rate reserve (adjusted for beta-blocker medications). The test was terminated more often because of perceived exertion (93/195) than because of heart rate limits (60/195). Four patients (2.1%) exhibited exercise-induced horizontal or downsloping ST segment depression of ≥1 mm. Except for 1 patient, the heart rate at test termination was comparable with the heart rate associated with the onset of the ECG abnormality. Conclusion: A graded submaximal exercise test without ECG but with symptom monitoring and conservative heart rate and perceived exertion endpoints may facilitate safe exercise intensities early after stroke. Symptom-limited exercise testing with ECG is still recommended when progressing to higher intensity exercise. Impact: Concerns about cardiovascular risk are a barrier to physical therapists implementing aerobic exercise in stroke rehabilitation. This study showed that, in the absence of access to exercise testing with ECG, submaximal testing with conservative heart rate and perceived exertion endpoints and symptom monitoring can support physical therapists in the safe prescription of aerobic exercise early after stroke. Lay Summary: It is recommended that people with stroke participate in aerobic exercise as early as possible during their rehabilitation. A submaximal exercise test with monitoring of heart rate, perceived exertion, blood pressure, and symptoms can support physical therapists in safely prescribing that exercise.